2018
DOI: 10.1001/jamapediatrics.2018.3115
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Prenatal Phthalate Exposure With Language Development in Early Childhood

Abstract: Prenatal exposure to phthalates has been associated with neurodevelopmental outcomes, but little is known about the association with language development. OBJECTIVE To examine the association of prenatal phthalate exposure with language development in children in 2 population-based pregnancy cohort studies. DESIGN, SETTING, AND PARTICIPANTS Data for this study were obtained from the Swedish Environmental Longitudinal Mother and Child, Asthma and Allergy (SELMA) study conducted in prenatal clinics throughout Vä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 62 publications
2
37
1
Order By: Relevance
“…Prenatal MEP concentrations found in the studied population were associated with increased risk of peer relationship problems. The existing studies, although not fully conclusive, report that prenatal exposures to phthalates might be associated with Attention Deficit and Hyperactivity Disorder (ADHD), autism spectrum disorder (ASD) and other specific behavioural problems (Bellinger, 2013;Miodovnik et al, 2014;Ejaredar et al, 2015;Katsikantami et al, 2016;Vrijheid et al, 2016;Braun, 2017;Lee et al, 2018;Bornehag et al, 2018,). Our findings are in agreement with the Mount Sinai Children's Environmental Health study in the US where prenatal phthalate exposure was associated with childhood social impairment at age of 7-9 years (Miodovnik et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Prenatal MEP concentrations found in the studied population were associated with increased risk of peer relationship problems. The existing studies, although not fully conclusive, report that prenatal exposures to phthalates might be associated with Attention Deficit and Hyperactivity Disorder (ADHD), autism spectrum disorder (ASD) and other specific behavioural problems (Bellinger, 2013;Miodovnik et al, 2014;Ejaredar et al, 2015;Katsikantami et al, 2016;Vrijheid et al, 2016;Braun, 2017;Lee et al, 2018;Bornehag et al, 2018,). Our findings are in agreement with the Mount Sinai Children's Environmental Health study in the US where prenatal phthalate exposure was associated with childhood social impairment at age of 7-9 years (Miodovnik et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…However, reported effects are not fully consistent across the different phthalate compounds, the neuropsychological domains implicated and the sex-specificity of the effects (Bellinger, 2013;Miodovnik et al, 2014;Ejaredar et al, 2015;Katsikantami et al, 2016;Vrijheid et al, 2016;Braun, 2017;Lee et al, 2018;Bornehag et al, 2018;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 98%
“…However, findings are not fully conclusive; inconsistencies across studies may be due to differences in analysed phthalates and their metabolites (usually few phthalates have been measured), the time of exposure assessment (prenatal and/or postnatal periods), misclassification of exposure, differences in neurodevelopmental domains assessed or child age at evaluation, to mention but a few. The sex-specificity of the neurodevelopmental effects is also underlined in some publications (Ejaredar et al, 2015;Vrijheid et al, 2016;Bornehag et al, 2018). As far as mechanisms of developmental neurotoxicity, experimental studies have indicated that several pathways relevant to brain development are targeted by phthalates, including dopaminergic neurotransmission (Chen et al, 2011;Dhanya et al, 2003;Tully et al, 2000;Wang et al, 2016), thyroid hormone homeostasis (Liu et al, 2015), and steroids' action through their receptors (Dombret et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is a public health concern on the effects of phthalate exposures, including their impact on child neurodevelopment. The existing studies to date suggest that both prenatal and postnatal phthalate exposures might be associated with behavioral problems and cognitive decrement in children (Ejaredar et al, 2015;Katsikantami et al, 2016;Vrijheid et al, 2016; Braun, 2017; Lee et al, 2018;Bornehag et al, 2018). However, findings are not fully conclusive; inconsistencies across studies may be due to differences in analysed phthalates and their metabolites (usually few phthalates have been measured), the time of exposure assessment (prenatal and/or postnatal periods), misclassification of exposure, differences in neurodevelopmental domains assessed or child age at evaluation, to mention but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were usually limited to one or two metabolic factors such as body-mass index and result of maternal diet and fatty acid metabolism [21][22][23], smoking [24] vitamin D [25][26][27][28][29][30][31][32][33][34] and folate supplementation [35][36][37][38][39][40][41][42][43], paracetamol [44,45], valproic acid, thalidomide, and antidepressants [13,46,47], and phthalates [48]. Maternal defects in one-carbon metabolism have also been proposed to influence ASD risk [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%